DENTAL HEALTH STATUS BASED ON DMFT AND TOOTH BRUSHING BEHAVIOR AS AN EFFORTS TO PREVENT PULP AND PERIAPICAL TISSUE DISEASES - Sri Purwanti; Ananda Putri Latifah; Adelvia Pramudita Balqis; Nasya Andini Salsabila (Dentin, 2025)
ABSTRACTBackground: The most common dental health problem in Indonesia is dental caries, with a prevalence of 45.3%. Indonesian people experience oral and dental health problems at a rate of 57.6%, with a DMF-T score of 7.1%. The prevalence of dental caries among children aged 10–14 years is 73.4%. Pulp and periapical tissue diseases are the most frequent conditions, with 17,480 cases, and they rank first among oral and dental diseases with a total of 405 cases. Objective: To describe dental health based on the DMFT index and toothbrushing behavior among students of SDN Karang Mekar based on characteristics such as frequency of dental visits, frequency of toothbrushing, frequency of toothbrush replacement, and the habit of brushing teeth after consuming sweet foods. Methods: This study used a descriptive observational survey with a cross-sectional approach. The target population consisted of 240 students aged 10–12 years. The sampling technique used was purposive sampling, involving 50 students who completed a questionnaire. Respondent data were then analyzed descriptively using statistical tests. Results: The frequency distribution of dental health status based on dental visits showed that 35 students (65%) were dominated by those who visited the dentist 1–2 times per year. The most common toothbrushing frequency was twice daily, reported by 28 students (52%). Almost all students replaced their toothbrushes when the bristles were no longer straight, accounting for 38 students (70%). Conclusion: The majority of students had fairly good toothbrushingKeywords: Behavior, Dental Health, Pulp Disease ABSTRAKLatar Belakang: Masalah kesehatan gigi paling umum di Indonesia adalah karies dengan presentase 45,3%. Masyarakat Indonesia mengalami masalah kesehatan gigi dan mulut sebesar 57,6%, dengan skor DMF-t 7,1%. Prevalensi karies gigi pada usia usia 10-14 tahun sebesar 73,4%. Penyakit pulpa dan jaringan periapikal merupakan penyakit terbanyak yaitu sebanyak 17.480 dan penyakit pulpa serta jaringan periapikal menduduki peringkat pertama untuk penyakit gigi dan mulut yaitu sebanyak 405. Tujuan: Memberikan gambaran kesehatan gigi berdasarkan DMFT dan perilaku menyikat gigi pada siswa SDN Karang Mekar berdasarkan karakteristik frekuensi kunjungan ke dokter gigi, frekuensi menyikat gigi, frekuensi mengganti sikat gigi dan frekuensi kebiasaan sikat gigi setelah makan makanan manis. Metode: Menggunakan survei deskriptif observasional dengan metode pendekatan cross sectional. Target populasi dalam penelitian ini sebanyak 240 siswa yang berusia 10-12 tahun. Teknik sampel yang digunakan yaitu purposive sampling yang berjumlah 50 siswa yang akan mengisi kuesioner. Data responden kemudian dilakukan analisis secara deskriptif menggunakan uji statistik. Hasil: Distribusi frekuensi gambaran status Kesehatan gigi pada kunjungan ke dokter gigi didapatkan hasil 35(65%) didominasi yang berkunjung ke dokter gigi sebanyak 1 atau 2 kali setahun, frekuensi menyikat gigi terbanyak 2x sehari sebesar 28(52%). Hampir semua siswa mengganti sikat gigi ketika bulu sikat tidak lurus lagi sebanyak 38(70%). Kesimpulan: Mayoritas siswa memiliki kebiasaan menyikat gigi cukup baik, siswa menyikat gigi diwaktu yang dianjurkan. Durasi dan penggantian sikat gigi yang dilakukan merupakan durasi ideal. Siswa mengganti sikat gigi setiap 3 bulan sekali, dan mengganti sikat gigi ketika bulunya tidak lurus lagi. Kata Kunci : Perilaku, Kesehatan Gigi, Penyakit Pulpa